2017
DOI: 10.12692/ijb/11.5.126-139
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of shoot induction and proliferation protocol for olive cultivars by assessing morpho-physiologic effects of pre-cooling and growth regulators

Abstract: To set a definite micro-propagation protocol for olive has always remained a challenging task owe to its woody nature. This study was consist of different olive cultivars (Arbosana, Arbequina, Koroneiki and Sorany) to devise a comprehensive shoot induction and proliferation protocol of olive media supplemented with various combinations of growth regulators (zeatin and BAP) and pre-cooling treatments (0, 24 and 48 hours). The in vitro performance of all the cultivars was assessed using a range of parameters inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…It was also reported that each cultivar responds varyingly to plant growth regulators [36]. Shoot regeneration via nodal explant in olive has been generally accomplished through zeatin, BAP, TDZ and GA 3 in previous studies [28,37].…”
Section: Discussionmentioning
confidence: 99%
“…It was also reported that each cultivar responds varyingly to plant growth regulators [36]. Shoot regeneration via nodal explant in olive has been generally accomplished through zeatin, BAP, TDZ and GA 3 in previous studies [28,37].…”
Section: Discussionmentioning
confidence: 99%